CERAMAH AGAMA DAN MUROTTAL AL-QUR’AN SEBAGAI INTERVENSI SPIRITUAL UNTUK PENINGKATAN PSIKOLOGIS PASIEN STROKE - Wahyuni, Sri; Dewi Setiawati; Lestari Rahmah (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
This study examines the effectiveness of Islamic spiritual interventions Qur’anic recitation (murottal) and religious sermons